PERSEPSI MAHASISWA MENGENAI MATA KULIAH SOCIAL SKILL DALAM MENGEMBANGKAN SOCIAL CONCERN MAHASISWA PPKN FKIP UNIVERSITAS LAMPUNG - Elsa Aura Savana; Devi Sutrisno Putri; Nurhayati Nurhayati; Ana Mentari; Dian Permata Sari (STKIP Subang, 2026)
This study was conducted to examine the problem of how students’ perceptions of the Social Skills course contribute to the development of social concern among students of the Pancasila and Citizenship Education (PPKn) Study Program, Faculty of Teacher Training and Education, University of Lampung. The research aimed to determine the extent to which students’ perceptions of the course are related to the development of their social concern. A quantitative approach with a descriptive research design was employed. The population consisted of 208 PPKn students from the 2022 and 2023 cohorts, and a sample of 67 respondents was selected using simple random sampling. Data were analyzed using frequency distribution analysis to describe students’ perceptions of the Social Skills course and the level of social concern development. The findings revealed that students generally had positive perceptions of the Social Skills course, and these perceptions played an important role in fostering social concern. Through case-based learning activities, students were able to actualize social skills in real-life situations, both within the campus environment and in the broader community. The study concludes that the Social Skills course not only enhances students’ academic competencies but also strengthens their social character as prospective educators and responsible, caring citizens.